1997
DOI: 10.3758/bf03211868
|View full text |Cite
|
Sign up to set email alerts
|

Visually perceived location is an invariant in the control of action

Abstract: Weprovide experimental evidence that perceived location is an invariant in the control of action, by showing that different actions are directed toward a single visually specified location in space (corresponding to the putative perceived location) and that this single location, although specified by a fixed physical target, varies with the availability of information about the distance of that target. Observers in two conditions varying in the availability of egocentric distance cues viewed targets at 1.5, 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 51 publications
5
98
3
2
Order By: Relevance
“…This could either involve navigating to a location that participants have previously seen before being blindfolded (Elliott, 1987;Philbeck et al, 1997), or returning to the starting position of a single-element (Mittelstaedt and Mittelstaedt, 2001) or multielement (Loomis et al, 1993) path. Across such studies, participants are very systematic in the errors that they make, demonstrating the existence of clear nonrandom principles underlying performance.…”
Section: Development Of Path Integrationmentioning
confidence: 99%
“…This could either involve navigating to a location that participants have previously seen before being blindfolded (Elliott, 1987;Philbeck et al, 1997), or returning to the starting position of a single-element (Mittelstaedt and Mittelstaedt, 2001) or multielement (Loomis et al, 1993) path. Across such studies, participants are very systematic in the errors that they make, demonstrating the existence of clear nonrandom principles underlying performance.…”
Section: Development Of Path Integrationmentioning
confidence: 99%
“…Yet a number of recent studies using "visually directed action", such as blind walking toward a previewed target, have demonstrated that perception of egocentric distance under similar conditions is both linear in physical distance and accurate out to at least 20 m (Elliott, 1986(Elliott, , 1987Fukusima, Loomis, & DaSilva, 1997;Loomis et al, 1992;Loomis, Klatzky, Philbeck, & Golledge, 1998;Philbeck, Loomis, & Beall, 1997;Rieser, Ashmead, Talor, & Youngquist, 1990;Sinai, Ooi, & He, 1998;Steenhuis & Goodale, 1988;Thomson, 1983; for a summary see Loomis and Knapp [in press]). The accuracy with which egocentric distance is perceived appears to conflict with the systematic misperception of shape and extent under similar conditions.…”
mentioning
confidence: 99%
“…Participants verbally estimated the egocentric distance and diameter of each target sphere. Participants then performed an indirect blind walking task (also called "triangulated walking") to the various targets (Loomis, Klatzky, Philbeck, & Golledge, 1998;Philbeck, Loomis, & Beall, 1997;Thompson et al, 2004). Participants viewed the target and then, while wearing a blindfold, first walked along a straight path oblique to the target and then turned and walked the rest of the way to the estimated target location.…”
mentioning
confidence: 99%